2014
DOI: 10.1111/pan.12485
|View full text |Cite
|
Sign up to set email alerts
|

Blood transfusion in patients treated with surgery for necrotizing enterocolitis

Abstract: Patients having necrotizing enterocolitis with bowel resection are more likely to need preoperative transfusion with packed red blood cells, which may be more necessary when surgery is longer, preoperative hematocrit is lower, and estimated blood loss is higher.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…8,9 It has been shown that in patients with severe NEC who underwent bowel resection, preoperative requirement of red blood cell (RBC) transfusions is increased. 10 The relationship between the timing of the transfusion and outcome of NEC has also been under investigation. 9 Some authors have suggested that judicious use of transfusions may diminish the severity of NEC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8,9 It has been shown that in patients with severe NEC who underwent bowel resection, preoperative requirement of red blood cell (RBC) transfusions is increased. 10 The relationship between the timing of the transfusion and outcome of NEC has also been under investigation. 9 Some authors have suggested that judicious use of transfusions may diminish the severity of NEC.…”
Section: Introductionmentioning
confidence: 99%
“…8 9 It has been shown that in patients with severe NEC who underwent bowel resection, preoperative requirement of red blood cell (RBC) transfusions is increased. 10…”
Section: Introductionmentioning
confidence: 99%